A meta-synthesis about the study of men's sexual behavior through the lens of hegemonic masculinity - Grave,Rita (2020)
The aim of this study is to understand how men experience sexual behavior in relation to dominant masculine norms in heteronormative social organizations. After a systematic search and a careful study selection process, we analyzed 15 scientific qualitative studies on men's sexual practices that draw on hegemonic masculinity. We then carried out a thematic synthesis of the results that collectively covered 438 male narratives ranging in age from 11 to 71. The results include (hetero)sex as a signifier of manhood, male sexual collectivity; sexual hierarchies; sexual risk; and the invisibility of sexual diversity. This meta-synthesis emphasizes the complex relationship between male sexuality and the influence of hegemonic masculinity, revealing important health and well-being effects on men. Also, this highlights a dynamic relationship that affects not only men but also their partners in sexual relationships.